A gender relations study of different occupational groups in Sambir village, Asajaya - Lee, Amelia Sze Chui (Faculty of Social Sciences, 2002)
This study aims to compare the gender relation of different occupational groups in Sambir, Asajaya. Factors that are included in this study are division of labour, access to and control over resources and participation in decision-making. selected literature reviews from previous studies are revealed to further enhance the understanding of researcher.